“We Thought We Were Alone”: The Subjective Experience of the Siblings of Anorexic Adolescent Patients - Persico, Angelo; Grandclerc, Salome; Giraud, Catherine; Moro, Marie Rose; Blanchet, Corinne (Frontiers in Psychiatry, 2021)
Objective: The siblings of patients suffering from Anorexia Nervosa (AN) are potentially affected by a disturbed emotional experience that often remains undetected. In order to bring them a psychological support, the Maison de Solenn proposed a support group program for these siblings. The current research explores their mental representations of AN and their emotional experience in the support group named “sibling group.” Method: This exploratory study is based on a phenomenological and inductive qualitative method. Four girls and three boys aged between 6 and 19 participating in the “sibling group” were included in a one-time focus group session using a semi-structured interview guide. The thematic data analysis was performed by applying the methods of interpretative phenomenological analysis. Results: Themes that emerged from the interview fall into four categories: AN explained by siblings; the individual emotional experience of siblings; the family experience of siblings and the experience inside the “sibling group.” Discussion: According to our participants, the “sibling group” thus functions as a good compromise between keeping an active role in the anorexic patient's care and taking a step back to avoid being eaten up by the illness. Sibling-group participants retrieved a sense of belonging, which is normally one of the functions of being a sibling. It is important to note that the “sibling group” is part of the comprehensive (or global) family-based approach included in an institutional multidisciplinary integrative care framework.